Emission turn-on and solubility turn-off in conjugated polymers: one- and two-photon-induced removal of fluorescence-quenching solubilizing groups - Schelkle, Korwin; Becht, Steffy; Faraji, Shirin; Petzoldt, Martin; Buckup, Tiago; Dreuw, Andreas; Motzkus, Marcus; Hamburger, Manuel (Macromolecular rapid communications, 2015)
The synthesis of highly efficient two-photon uncaging groups and their potential use in functional conjugated polymers for post-polymerization modification are reported. Careful structural design of the employed nitrophenethyl caging groups allows to efficiently induce bond scission by a two-photon process through a combination of exceptionally high two-photon absorption cross-sections and high reaction quantum yields. Furthermore, π-conjugated polyfluorenes are functionalized with these photocleavable side groups and it is possible to alter their emission properties and solubility behavior by simple light irradiation. Cleavage of side groups leads to a turn-on of the fluorescence while solubility of the π-conjugated materials is drastically reduced.